Character Education Values in the Islamization of Sunan Sendang Duwur in History Learning - Silviyana Damayanti; Dyah Kumalasari (Universitas Pendidikan Ganesha, 2025)
The rapid flow of globalization has brought various influences to the life of a nation, including the quality of education in Indonesia. Therefore, Indonesia requires a generation that is not only intelligent but also possesses strong character, upholds religious values, and is capable of addressing various problems such as violence, bullying, misuse of technology, intolerance, and lack of politeness. This study aims to strengthen character education values through the exemplary life of Sunan Sendang Duwur in history learning. The research was conducted at the Sunan Sendang Duwur tomb complex. The study employed a qualitative descriptive design by describing and presenting the conditions as they actually occur. In addition, a historical approach was used, consisting of five stages: topic selection, source collection, verification, interpretation, and historiography. From these stages, the researcher was able to classify the findings, which indicate the presence of character education values embedded in the Islamization carried out by Sunan Sendang Duwur. Religious values, tolerance, social care, love of peace, and environmental awareness can be internalized by students as part of efforts to strengthen and habituate these values in daily life.